A Study to Assess the Lived in Experience of Corona Positive Patients in Selected Community Area, Kanyakumari District - Merlin Suja C.R.; Arul Sili Ninchal A. (International Journal of Community Health Nursing And Practices, 2023)
Aim: To assess the lived-in experience corona positive parents among community people. Methodology: A Qualitative study design was used to assess the lived-in experience of corona positive patients among the community people at selected community area. There were 9 samples are selected by sampling technique. The samples shared their experience when they suffered from corona virus. Results: The study findings were said that the physical sufferings of the patients and their social adjustments and their psychological conditions such as fear and anxiety about hearing the death news of Covid-19 positive patients and their emotions were also shared by the patients. Conclusion: Since the samples were shared their lived-in experience of corona virus. By this Information of corona positive patients, well understood the knowledge of lived in experience of corona positive patients.
Keywords: COVID-19; Corona; Corona positive patients; Lived in experience